The Social Relations of Ethnographic Fieldwork: Access, Ethics and Research Governance - Shobha Nepali; Rochelle Einboden; Trudy Rudge (SAGE Publishing, 2023)
The focus of this methodological paper is to discuss the challenges of conducting fieldwork, using reflections from our experiences of accessing a research site for ethnographic data collection. The research project aimed to explore nurses' social relations in their workplace and the inequities between and within these relations among nurses of diverse social positions. Due to the sensitive nature of this topic, access to the research site posed several challenges and was further complicated by the bureaucratic ethics process that governs clinical sites in Australia. Although this study was considered a low and negligible risk research, negotiating the ethics process was full of hitches and hindrances resulting in the refusal of access. This paper offers ethnographers a reflection on challenges in accessing clinical sites to conduct research and a discussion of strategies that may be useful to navigate and counter these challenges by managing social relations in the field.